Biomimetic and NOS‐Responsive Nanomotor Deeply Delivery a Combination of MSC‐EV and Mitochondrial ROS Scavenger and Promote Heart Repair and Regeneration - Ning Zhang; Mengkang Fan; Yongchao Zhao; Xiaolong Hu; Qiongjun Zhu; Xiaolu Jiao; Qingbo Lv; Duanbin Li; Zheyong Huang; Guosheng Fu; Junbo Ge; Hongjun Li; et al. (Advanced Science, 2023)
Abstract Mesenchymal stem cell‐derived extracellular vesicle (MSC‐EV) is shown to promote cardiac repair, however, it still falls short in initiating myocardia proliferation restart. In this regard, ROS‐induced DNA damage and responses are the culprit of cellcycle arrest. Here, this work constructs a hybrid cell‐derived extracellular vesicle that is composed of MSC and macrophage membranes and encompasses MitoN, a ROS scavenger, to boost the healing of the heart. The MitoN, a NAD(P)H mimic, could target the mitochondrial to eliminate the ROS resuming the arrested cell cycle. The hybrid extracellular vesicle (N@MEV) could respond to the inflammatory signals generated during myocardial injury and thus enable superior targeting and enrichment to the location of the damage. L‐arginine, which could be catalyzed by NOS and ROS into NO and SO provide a driving force, is immobilized within the vesicle (NA@MEV) to further enhance the N@MEV's potential to penetrate the cardiac stroma. In combination with multiple mechanisms, NA@MEV increased heart function 1.3‐fold EF% versus MSC‐EV in mouse myocardial injury model. A more in‐depth mechanistic study found that the NA@MEV could modulate M2 macrophage; promote angiogenesis; reduce DNA damage and response, and thereby restart cardiomyocyte proliferation. Thus, this combined therapy shows synthetic effects in heart repair and regeneration.